2016
DOI: 10.1080/01621459.2015.1075407
|View full text |Cite
|
Sign up to set email alerts
|

Priors for Random Count Matrices Derived from a Family of Negative Binomial Processes

Abstract: We define a family of probability distributions for random count matrices with a potentially unbounded number of rows and columns. The three distributions we consider are derived from the gamma-Poisson, gamma-negative binomial, and beta-negative binomial processes, which we refer to generically as a family of negative-binomial processes. Because the models lead to closed-form update equations within the context of a Gibbs sampler, they are natural candidates for nonparametric Bayesian priors over count matrice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 35 publications
0
45
0
Order By: Relevance
“…Note that if we fix q j = 1 for all j, then the proposed NBP with sample-specific scaling parameters reduces to the NBP in Zhou and Carin [2015] and Zhou et al [2016].…”
Section: Nbp-seq: Negative Binomial Process For Rna-seqmentioning
confidence: 99%
See 4 more Smart Citations
“…Note that if we fix q j = 1 for all j, then the proposed NBP with sample-specific scaling parameters reduces to the NBP in Zhou and Carin [2015] and Zhou et al [2016].…”
Section: Nbp-seq: Negative Binomial Process For Rna-seqmentioning
confidence: 99%
“…possible ways to the columns of N J . Similar to the derivation in Zhou et al [2016], using a marginalization procedure shown in Caron et al [2014], one may marginalize out the gamma process G, leading to the distribution of the random count matrix as…”
Section: Nbp-seq: Negative Binomial Process For Rna-seqmentioning
confidence: 99%
See 3 more Smart Citations